The Role of Age in Creating Difference and Linguistic Variation in Social Occasions and Domains (Raparin Journal of Humanities (RJH), 2025)
This research is entitled with (The role of age in creating difference and linguistic variation in social occasions and domains), and aims to show the effect of age as a social factor in language variation and different expression and patterns in different events and social areas. In his research, the researcher followed the descriptive analytical method, and took examples and research models from the community.The researcher divided his research into two topics:The first topic is devoted to linguistic variation and age, which discusses the concept and emergence of sociolinguistics and linguistic variation, dimensions and objectives of sociolinguistics, language change and linguistic variation, then the relationship between language and age, age and social factors and gender, the relationship between age and style, the relationship between age and culture), age and social laws, age and social norms, age and respect.The second topic is dedicated to the differences in the use of expressions according to age in social occasions and areas (funerals, swearing, greeting) with examples of current expressions and speeches of the central Kurdish dialect.    Finally, the most important results, list of sources and a summary of the study are presented in English.